EFFECTIVE COATING OF SPACE BY COORDINATION SPHERES – THE BASIC PRINCIPLE OF STRUCTURE AND CONSTITUTION OF MINERALS - E.P. Makagonov (Минералогия)
The structures of minerals are considered as an effective coating of space by coordination spheres (ECS principle). Coating is a space, each point of which belongs to one or several shapes. The rules of construction of mineral structures are given according to ECS principle. The basic coordination of particles in crystals of minerals is caused by these rules. The densest packages are special cases. The ECS structures correspond to the supergroups of minerals according to the rules of the Commission on New Mineral Nomenclature and Classification of the International Mineralogical Association. The examples of supergroups of minerals (garnet, apatite, alunite) are presented. The ECS structures are linked with chemical particles via distribution by nl-states and crystal lattice vibrations.